Credit, Debt and the Omani Community in Zanzibar in the late nineteenth century - Harthi, Amira Sulaiman Ali al- (Durham University, 2025)
Despite the expanded literature of Omani history in Zanzibar in the nineteenth century, few studies have been focused on the patterns of credit and debt of them. This thesis examines the nature of Omani community in living with others and how people made decisions about what sort of business to do, whom to borrow from or lend to, and whom to do business with. Using a sample of one thousand transactions to illustrate the idea of credit and debt patterns between Omanis and other groups that lived in Zanzibar. This study offers a problematic argument of nisba and raising a question of who was giving nisbas to these people. This study presents the active roles of women as moneylenders and borrowers, and how the social rank is reflected in dress and clothing styles. Through an analysis of these transactions, this thesis explores the different approaches of cosmopolitan Zanzibar and how these various meanings can be seen through the credit and debt process of a diverse people living in Zanzibar. Also, we conclude that there are two distinct ways of understanding cosmopolitanism in Zanzibar through transactions. Firstly, Zanzibar society in the nineteenth century involved people from various ethnicities and backgrounds, which might be seen as a kind of cosmopolitanism involving ‘modernity’ and ‘openness’ to different cultures. Secondly, the society that included multiethnic people, could be seen as divided and categorised by their status and ethnicity
Keywords: Commerce -- Zanzibar -- 19e siècle

Customs House, Steamers, and the Entrepôt: Zanzibar Trade Infrastructure Circa 1830–1888 - Pawełczak, Marek (African Economic History, 2020)
Keywords: Commerce -- Zanzibar -- 19e siècle

The Ivory Trade and Political Power in Nineteenth-Century East Africa - Gooding, Philip (Animal Trade Histories in the Indian Ocean World, 2020)
This chapter analyses ivory consumption and trade in the context of shifting political power in nineteenth-century East Africa. It firstly describes how increased demand for ivory and ivory products in the wider Indian Ocean World, Europe, and North America contributed to a decline in ivory’s ownership, usage, and display in East Africa. It then examines the nature and construction of Omani and coastal East African communities in East Africa’s interior to show how political power became increasingly tied to access and control the ivory trade. In nineteenth-century East Africa, ivory was transformed from a product with significant symbolic capital to one whose history was increasingly shaped by capitalistic forces.
Keywords: Commerce -- Zanzibar -- 19e siècle

Paper Routes: Inscribing Islamic Law across the Nineteenth-Century Western Indian Ocean - Bishara, Fahad Ahmad (Law and History Review, 2014)
Sometime during the middle of the nineteenth century, a correspondent from the interior of Oman wrote to the jurist Sa‘id bin Khalfan Al-Khalili (c. 1811–70) with an observation: “The Mazru‘is have wealth on the Swahili coast [al-Sawāḥil] and wealth in Oman.” This in itself was no surprise: the Mazru‘is, along with scores of other Arab clans, included a branch that had long since established its political authority in Mombasa, on the coast of what is now Kenya, but lately, the correspondent suggested, things had been changing. Members of the Mombasa Mazru‘is were now coming to Oman armed with wakalas (powers of attorney) from unknown scribes, for the sale of their familial properties in their ancestral homeland. “He [the Mazru‘i] sold what God likes from these properties and took the value… and the yield was separated from the property owners.” The people's acquiescence to the state of affairs was of particular surprise to the questioner. Days, months, and years went by, he noted, and the property owners (arbāb al-amwāl) did not seem the least bit interested in changing the system, “and the people, as you well know, come and go via this sea, from Oman to the Swahili coast, with confidence that they know [bi-ḥukm al-iṭma'ināna annahum ‘alamū].”
Keywords: Commerce -- Zanzibar -- 19e siècle

A Sea of Debt: Histories of Commerce and Obligation in the Indian Ocean, c. 1850-1940 - Bishara, Fahad Ahmad (Duke University, 2012)
Keywords: Commerce -- Zanzibar -- 19e siècle